MEMBANDINGKAN PERFORMA ANTARA HYPERLEDGER DAN MYSQL - Riko Herwanto; Onno W. Purbo; Sriyanto Sriyanto (IIB Darmajaya, 2020)
In this paper, we report the benchmarking results of Hyperledger, a Distributed Ledger, which is the derivation Blockchain Technology. Method to evaluate Hyperledger in a limited infrastructure is developed. The measured infrastructure consists of 8 nodes with a load of up to 20000 transactions/second.. The benchmarking of Hyperledger shows better than a database system in a high workload scenario. We found that the maximum size data volume in one transaction on the Hyperledger network is around ten (10) times of MySQL. Also, the time spent on processing a single transaction in the blockchain network is 80-200 times faster than MySQL. This initial analysis can provide an overview for practitioners in making decisions about the adoption of blockchain technology in their IT systems.